Prevalence and Predictors of Sleep Disturbance among Liver Diseases in Long-Term Transplant Survivors - Mamatha Bhat; Jonathan M Wyse; Erica Moodie; Peter Ghali; Nir Hilzenrat; Philip Wong; Marc Deschênes (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Patients with cirrhosis are known to experience sleep disturbance, which negatively impacts health-related quality of life.